Establishing Normal Range of Fetal Pulmonary Artery and Fetal Aortic Diameter in 18-26 Weeks of Gestation in Pakistani Population - Beenish Nadeem, Naushaba Malik, Manal Niazi, Saira Ahmad, Mariam Hassan Bukhari, Arsalan Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Congenital heart diseases constitute almost 0.8 to 1.2% of newborn illnesses globally however unfortunately 64% of them remained undiagnosed on conventional anamoly scan which uses four chamber view for cardiac evaluation. In developed countries, other than routine anomaly scan, the three vessel view(3VV) has been added to look for any potential outflow tract anomalies which increased the sensitivity of screening CHD however this view is not routinely used in our clinical practice due to lack of expertise and less awareness regarding the importance of this view . We aimed to establish normal reference values of fetal pulmonary and fetal aorta diameter value using 3VV so that its routine use can increase diagnostic accuracy of anamoly scan in our population. Methodology: This is a non probability convenient study investigating healthy pregnant females between 18-26weeks of gestation conducted from 04-02-2022 to 04-08-2022. After formal ethical approval, 56 patients were included in the study. After achieving 3VV,fetal pulmonary artery and fetal aorta diameter were evaluated and mean values were calculated for each gestational week. Results: The mean age of pregnant females included is 27.3 + 4.4 years (range 20 -37 years). The pulmonary artery diameter ranged from 2.3mm at 18 week of gestation to 3.6mm at 26 week of gestation. Fetal PAD is observed to correlate linearly (r=0.887) with gestational age and linear regression equation derived as PAD= (-0.52) +0.15(GA). Mean fetal aortic diameter was calculated ranged from 1.5mm at 18 week of gestation to 1.6mm at 26week of gestation. Fetal aorta diameter correlation with gestational was found to be 0.164 showing weak correlation along with insignificant regression analysis hence the regression equation cannot be formulated for fetal aorta. Conclusion: Normal mean values of fetal pulmonary artery and fetal aorta from 18-26weeks of gestation were calculated. Linear relationship was found between pulmonary artery diameter and gestational age. However weak correlation noted between fetal aorta diameter and gestational age was noted. Keywords: Fetal pulmonary artery; fetal aorta; anamoly scan; three vessel view(3VV); normal range.